Do Regulatory and Curriculum Requirements for Interprofessional Practice Align? - Brownie S; Tokolahi E; Broman P; Haggie M; Andersen P (Journal of Multidisciplinary Healthcare, 2023)
Sharon Brownie,1– 3 Ema Tokolahi,4 Patrick Broman,3 Marrin Haggie,3 Patrea Andersen3,5,6 1School of Health Sciences, Swinburne University of Technology, Melbourne, VIC, Australia; 2School of Health Sciences and Social Work, Griffith University, Gold Coast, QLD, Australia; 3Centre for Health and Social Practice, Wintec Te Pūkenga, Hamilton, New Zealand; 4School of Occupational Therapy, Otago Polytechnic Te Pūkenga, Dunedin, New Zealand; 5School of Health, University of the Sunshine Coast, Sippy Downs, QLD, Australia; 6School of Health, Medical and Applied Sciences, Central Queensland University, Rockhampton, QLD, AustraliaCorrespondence: Sharon Brownie, School of Health Sciences, Swinburne University of Technology, Hawthorn, Victoria, Australia, 3122, Email sbrownie@swin.edu.auBackground: While interprofessional (IP) competency and Interprofessional Education (IPE) has received increasing attention in health, agreement on specific competencies and teaching approaches is frequently limited by profession-specific understandings. As part of a quality improvement initiative focused on improving delivery of IPE offerings, this enquiry maps current regulatory and curricula requirements for IP practice to health professional students from 12 professions trained across Aotearoa New Zealand’s national vocational education provider.Methods: Requirements for IP competency in national accreditation documents and in an operative teaching curricula were mapped for 12 professions, namely, clinical exercise physiology, counselling, massage, medical radiology, midwifery, nursing, occupational therapy, osteopathy, paramedicine, physiotherapy, social work, and sport and exercise science. A desk audit was conducted to identify the presence of core IP competencies for each profession. This involved a four-step process 1) Examination of regulatory standards for each profession to confirm IP requirements for each profession; 2) Examination of an operative curricula from each profession to identify the presence and translation of IP regulatory requirements to each of the profession-specific programs of study; 3) Mapping to identify within domains the core (common) IP competencies across the professions, and 4) Consideration of the similarities and differences between accreditation documents and curricula.Results: Of 12 professions, 10 clearly identified IP competency as an expectation. Clinical Exercise Physiology and Counselling were exceptions with explicit requirement for IP competency not evident. Coordination and collaboration were the most identified competency domains in accreditation documents and curricula. In descending order of prevalence, communication, shared values, reflexivity, role-understanding, and teamwork were also identified requirements amongst the 10 professions with IP competency requirements.Conclusion: The IP competencies identified as common across professions can be used to inform development of teaching and assessment. Greater alignment between teaching curricula and required competency standards in this area is recommended.Keywords: interdisciplinary education, interdisciplinary communication, interprofessional relations, collaboration, competency